2003
DOI: 10.2527/2003.811143x
|View full text |Cite
|
Sign up to set email alerts
|

Beef Customer Satisfaction: Trained sensory panel ratings and Warner-Bratzler shear force values1

Abstract: Trained sensory panel ratings and Warner-Bratzler shear force (WBS) values from the Beef Customer Satisfaction study are reported. Carcasses were chosen to fit into USDA quality grades of Top Choice (upper two-thirds of USDA Choice), Low Choice, High Select, and Low Select. A trained, descriptive attribute panel evaluated top loin, top sirloin, and top round steaks for muscle fiber tenderness, connective tissue amount, overall tenderness, juiciness, flavor intensity, cooked beef flavor intensity, and cooked be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 11 publications
6
52
2
1
Order By: Relevance
“…Thus, the importance of sample preparation and evaluation setting should be emphasized. For example, Lorenzen et al (2003) reported a lower correlation (-0.26) of WBs values with ''in home'' consumer judgements and partially attributed the lack of relationship to the variation in steak preparation encountered during ''in home'' consumer studies. Several studies have been carried out employing a trained panel in order to establish threshold values of WBs for tenderness acceptability (Boleman et al, 1997;Miller et al, 1995;Miller et al, 2001;Shackelford, Morgan, Cross, & Savell, 1991;.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the importance of sample preparation and evaluation setting should be emphasized. For example, Lorenzen et al (2003) reported a lower correlation (-0.26) of WBs values with ''in home'' consumer judgements and partially attributed the lack of relationship to the variation in steak preparation encountered during ''in home'' consumer studies. Several studies have been carried out employing a trained panel in order to establish threshold values of WBs for tenderness acceptability (Boleman et al, 1997;Miller et al, 1995;Miller et al, 2001;Shackelford, Morgan, Cross, & Savell, 1991;.…”
Section: Resultsmentioning
confidence: 99%
“…Many Studies have shown that increased marbling level, or intramuscular fat (IMF%) was associated with greater tenderness, juiciness, flavour liking and overall liking (Lorenzen et al, 2003;Garmyn et al, 2011;Chriki et al, 2012;O'Quinn et al, 2012). Furthermore Thompson (2004) in cattle and in lamb found a positive relationship between IMF% and the flavour liking and juiciness scores of untrained Australian consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ageing time had a significant effect on pH, meat colour, WBSF, and myofibril fragmentation index of LL muscle. Lorenzen et al (2003) a low correlation of WBS values with ''in home'' consumer judgments; they partially attributed the low relationship to the high variability in steak culinary preparation in ''in home'' consumer studies. Correlations of WBSF with the sensory assessment of tenderness are known to be highly variable, showing r-values ranging from -0.32 to 0.94 (Caine et al 2003).…”
Section: Warner-bratzler Shear Forcementioning
confidence: 99%